Allostatic Load and Adverse Pregnancy Outcomes. Issue 6 (2nd December 2022) - Lueth, Amir J.; Allshouse, Amanda A.; Blue, Nathan M.; Grobman, William A.; Levine, Lisa D.; Simhan, Hyagriv N.; Kim, Jin Kyung; Johnson, Jasmine; Wilson, Fernando A.; Murtaugh, Maureen; Silver, Robert M.
Abstract : In a prospectively evaluated nulliparous cohort, allostatic load in early pregnancy is associated with adverse pregnancy outcomes, including hypertensive disorders of pregnancy. Abstract : OBJECTIVE: To assess the association between allostatic load, as an estimate of chronic stress, and adverse pregnancy outcomes. METHODS: This was a secondary analysis of nuMoM2b (Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be), a prospective observational cohort study. Our primary exposure was dichotomous high allostatic load in the first trimester, defined as 4 or more of 12 biomarkers in the "worst" quartile. The primary outcome was a composite adverse pregnancy outcome: hypertensive disorders of pregnancy (HDP), preterm birth, small for gestational age (SGA), and stillbirth. Secondary outcomes included components of the composite. Multivariable logistic regression was used to test the association between high allostatic load and adverse pregnancy outcomes, adjusted for potential confounders. Mediation and moderation analyses were conducted to assess the role of allostatic load along the causal pathway between racial disparities and adverse pregnancy outcomes. RESULTS: Among 4, 266 individuals, 34.7% had a high allostatic load. Composite adverse pregnancy outcome occurred in 1, 171 (27.5%): 14.0% HDP, 8.6% preterm birth (48.0% spontaneous and 52.2% indicated), 11.0% SGA, and 0.3% stillbirth. After adjustment for maternal age, gravidity, smoking, bleeding in the first trimester, and health insurance, high allostatic load was significantly associated with a composite adverse pregnancy outcome (adjusted odds ratio [aOR] 1.5, 95% CI 1.3, 1.7) and HDP (aOR 2.5, 95% CI 2.0–2.9), but not preterm birth or SGA. High allostatic load partially mediated the association between self-reported race and adverse pregnancy outcomes. The association between allostatic load and HDP differed by self-reported race, but not for a composite adverse pregnancy outcome, preterm birth, or SGA. CONCLUSION: High allostatic load in the first trimester is associated with adverse pregnancy outcomes, particularly HDP. Allostatic load was a partial mediator between race and adverse pregnancy outcomes. The association between allostatic load and HDP differed by self-reported race.